Newly qualified teachers in Trinidad and Tobago: Impact on/interaction with the system - Morris, Jeanette; Joseph, Arthur (School of Education, UWI, St. Augustine, 2001)
This monograph reports on a study that investigated the following: 1) experienced teachers' perceptions of the value of the present teachers' college programme, 2) how newly trained teachers are socialized into the school working culture, and 3) what happens to the knowledge and skills acquired at teachers' college. Interviews were conducted with eight newly qualified teachers (six females and two males) from five schools, and three principals. Classroom observation was also carried out with seven teachers. It was found that, on the whole, experienced teachers view their newly qualified counterparts as having positive attitudes to their work and displaying caring relationships with their students. However, they point out that where teaching methods are concerned, newly qualified teachers display some shortcomings. The experienced teachers admitted that there is little time and virtually no structured programme for inducting these teachers into the ways of life of the schools. In general, newly qualified teachers felt that the teachers' college programme did not prepare them adequately for work in the school setting. Despite this perception, the evidence, both from the interviews and the classroom observations, seemed to indicate that through professional training received by the newly qualified teachers, overwhelming benefits flowed to the schools
Keywords: MUSTER Project; Beginning teachers; Teacher effectiveness; Trinidad and Tobago